Use of Phototherapy in Children. Issue 2 (30th January 2017) - Eustace, Karen; Dolman, Sophie; Alsharqi, Ali; Sharpe, Graham; Parslew, Richard
Abstract: Background: Phototherapy is a well‐recognized treatment in adults and children. Previous articles have reported success in treating recalcitrant skin disorders such as atopic dermatitis (AD), psoriasis, pityriasis lichenoides chronica, and vitiligo in children. Methods: This was a retrospective review over an 18‐month period from June 2012 to December 2013 of all children receiving phototherapy in a tertiary pediatric dermatology center. Results: Seventy‐five patients 3 to 17 years of age (mean 10.6 years; 35 male, 40 female) were included. Forty‐eight (64%) patients had AD and 21 (28%) had psoriasis. Seventy received narrowband ultraviolet B (NBUVB) treatment and five received hand and foot psoralen and ultraviolet A (PUVA) treatment. All patients with AD were treated with NBUVB and four (8.3%) were also treated with hand PUVA. After phototherapy, 76% had documented clear to almost clear skin. At the 12‐month follow‐up, 52% of the patients with AD remained clear. All 21 patients with psoriasis underwent NBUVB phototherapy. The clearance rate after phototherapy was 86%. At the 12‐month follow‐up, 43% of the patients with psoriasis remained clear. Conclusion: Phototherapy can reduce disease burden in individuals with severe AD and psoriasis and should be considered as a second‐line therapy if standard topical regimens are unsuccessful.